2016
DOI: 10.1051/e3sconf/20160915002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil-Vegetation-Atmosphere Interaction on the Stability of a Clay Slope: A Case Study

Abstract: Abstract. Deep and slow landslide processes are frequently observed in clay slopes located along the Southern Apennines (Italy). A case study representative of these processes, named Pisciolo case study, is discussed in the paper. The geo-hydro-mechanical characteristics of the materials involved in the instability phenomena are initially discussed. Pluviometric, piezometric, inclinometric and GPS monitoring data are subsequently presented, suggesting that rainfall infiltration constitutes the main factor indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Mechanical soil properties, such as stiffness and strength, have traditionally monopolised the interest of practicing geotechnical engineers and researchers. The effect of pore water pressures (pwp) and of their variation on the stability and serviceability of geotechnical structures [1][2][3] and natural slopes [4,5], and on the coefficient of earth pressure at rest [6], has also long been recognised. Although, by association, the influence of hydraulic parameters, such as permeability and soil-water retention, is widely accepted in theory [7,8], in practice it is rare that complete and comprehensive laboratory and field data are dedicated to determining hydraulic parameters with accuracy and confidence, perhaps owing to the difficulty of the task.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical soil properties, such as stiffness and strength, have traditionally monopolised the interest of practicing geotechnical engineers and researchers. The effect of pore water pressures (pwp) and of their variation on the stability and serviceability of geotechnical structures [1][2][3] and natural slopes [4,5], and on the coefficient of earth pressure at rest [6], has also long been recognised. Although, by association, the influence of hydraulic parameters, such as permeability and soil-water retention, is widely accepted in theory [7,8], in practice it is rare that complete and comprehensive laboratory and field data are dedicated to determining hydraulic parameters with accuracy and confidence, perhaps owing to the difficulty of the task.…”
Section: Introductionmentioning
confidence: 99%
“…Engineered infrastructure slopes [1][2][3], i.e, slopes formed by excavating or compacting soil to accommodate highways, railways etc., and natural slopes [4,5] have long been known to be affected by interaction with the atmosphere due to the seasonal variation of pore water pressure [6], which affects the stresses, stiffness and the coefficient of earth pressure at rest [7]. For example, [2] observed that modestly vegetated slopes are prone to deep seated failures, primarily after wet periods, whereas densely vegetated slope suffer from severe serviceability problems, which are likely to occur towards the end of dry periods.…”
Section: Introductionmentioning
confidence: 99%
“…During and after excavation, the stress redistribution due to dewatering, unloading and swelling can initiate new cracks and fissures, or open the existing ones. Such discontinuities act as seepage paths which increase the permeability of the soil mass and subsequently affect the rate of NEPWP generation and dissipation (Vaughan and Walbancke, 2009, Eigenbrod, 1975, James, 1970a, Pedone et al, 2016, Vaughan and Walbancke, 1973, Griffiths and Li, 1993. Also, the dewatering and desaturating of soil may result in drying cracking (Hueckel et al, 2013, Peron et al, 2009.…”
Section: Introductionmentioning
confidence: 99%